Membangun Akhlak Anak melalui Pendidikan Keislaman di PAUD - Maryam, Siti; Utama, Ferdian (ALSYS, 2025)
The limited in-depth research on the internalization of moral values through Islamic education at the Early Childhood Education (PAUD) level underpins this study, given the critical importance of character formation from an early age. This research aims to analyze the strategies, implementation, as well as supporting and inhibiting factors in the development of children's moral character at PAUD Al-Ikhlas. A qualitative approach with a case study design was employed, and data were collected through interviews, observations, and document analysis involving the school principal, teachers, and parents. The findings reveal that the internalization of moral values is integrated across all school activities. Three main strategies are applied: modeling by all school members, habituation of Islamic values in daily routines, and value reinforcement through emotional media such as storytelling and nasyid. Key supporting factors include visionary leadership and strong partnerships between the school and parents, while the main obstacles involve inconsistencies between home and school values and fluctuations in teacher motivation. This study contributes to the reinforcement of social learning theory and the concept of tarbiyah, and has practical implications for the development of a holistic curriculum and stronger synergy between schools and families in fostering children's character development.